Prevalence of chronic obstructive pulmonary disease in asymptomatic smokers - Sansores, Raúl H (Int J Chron Obstruct Pulmon Dis, 2015)
BACKGROUND: Physicians do not routinely recommend smokers to undergo spirometry unless they are symptomatic. OBJECTIVE: To test the hypothesis that there are a significant number of asymptomatic smokers with chronic obstructive pulmonary disease (COPD), we estimated the prevalence of COPD in a group of asymptomatic smokers. METHODS: Two thousand nine hundred and sixty-one smokers with a cumulative consumption history of at least 10 pack-years, either smokers with symptoms or smokers without symptoms (WOS) were invited to perform a spirometry and complete a symptom questionnaire. RESULTS: Six hundred and thirty-seven (21.5%) smokers had no symptoms, whereas 2,324 (78.5%) had at least one symptom. The prevalence of COPD in subjects WOS was 1.5% when considering the whole group of smokers (45/2,961) and 7% when considering only the group WOS (45/637). From 329 smokers with COPD, 13.7% were WOS. Subjects WOS were younger, had better lung function and lower cumulative consumption of cigarettes, estimated as both cigarettes per day and pack-years. According to severity of airflow limitation, 69% vs 87% of subjects were classified as Global Initiative for Chronic Obstructive Lung Disease stages I–II in the WOS and smokers with symptoms groups, respectively (P<0.001). A multivariate analysis showed that forced expiratory volume in 1 second (mL) was the only predictive factor for COPD in asymptomatic smokers. CONCLUSION: Prevalence of COPD in asymptomatic smokers is 1.5%. This number of asymptomatic smokers may be excluded from the benefit of an “early” intervention, not just pharmacological but also from smoking cessation counseling. The higher forced expiratory volume in 1 second may contribute to prevent early diagnosis.